2014
DOI: 10.15381/rivep.v25i1.8471
|View full text |Cite
|
Sign up to set email alerts
|

DETERMINACIÓN DE LA SUSCEPTIBILIDAD ANTIBIÓTICA in vitro DE BACTERIAS SUBGINGIVALES EN CANINOS CON ENFERMEDAD PERIODONTAL MODERADA A SEVERA.

Abstract: Se determinó la susceptibilidad antibiótica de bacterias subgingivales en caninos con enfermedad periodontal moderada a severa. Se trabajó con 30 canes provenientes de cuatro albergues de la ciudad de Lima. Las muestras se tomaron con puntas de papel estéril colocadas en el fondo de la bolsa periodontal del cuarto premolar y canino del cuadrante superior derecho. El agente bacteriano aislado con mayor frecuencia fue Porphyromonas gingivalis (50%). Además, se hallaron Bifidobacterium spp (20%), Prevotella inter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
5
0
3

Year Published

2019
2019
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(10 citation statements)
references
References 9 publications
2
5
0
3
Order By: Relevance
“…Five studies reported data about AMR in E. coli recovered from pets. Of this, four were focused on dogs [43,69,70,71], while the remaining study considered a diversity of animals, including pets such as dogs, and also ducks and guinea pigs, which are consumed, or others including donkeys used in the agrarian setting [52]. Three of these studies were developed in Lima [43,69,70], one in Cajamarca (Northern Peru) [71], and the remaining study tested samples from 4 Peruvian regions, including Lima [52].…”
Section: Pet-isolated Escherichia Colimentioning
confidence: 99%
See 1 more Smart Citation
“…Five studies reported data about AMR in E. coli recovered from pets. Of this, four were focused on dogs [43,69,70,71], while the remaining study considered a diversity of animals, including pets such as dogs, and also ducks and guinea pigs, which are consumed, or others including donkeys used in the agrarian setting [52]. Three of these studies were developed in Lima [43,69,70], one in Cajamarca (Northern Peru) [71], and the remaining study tested samples from 4 Peruvian regions, including Lima [52].…”
Section: Pet-isolated Escherichia Colimentioning
confidence: 99%
“…Of this, four were focused on dogs [43,69,70,71], while the remaining study considered a diversity of animals, including pets such as dogs, and also ducks and guinea pigs, which are consumed, or others including donkeys used in the agrarian setting [52]. Three of these studies were developed in Lima [43,69,70], one in Cajamarca (Northern Peru) [71], and the remaining study tested samples from 4 Peruvian regions, including Lima [52]. As with E. coli of other origins, the number and type of antibiotics tested varied among the different studies, with AMR data of a total of 22 different antibacterial agents (Table 6).…”
Section: Pet-isolated Escherichia Colimentioning
confidence: 99%
“…Elaboración propia. (20) reportan en su estudio que la presencia de microbiota entérica en caninos con inicios de periodontitis se relaciona con ciertas condiciones del microambiente oral que facilita el crecimiento exacerbado de patógenos oportunistas sobre todo anaerobios, dado que el ambiente facilita su desarrollo. Entre las condiciones se encuentran las higiénico-sanitarias deficientes de los albergues, y la contaminación oro-fecal derivada de hábitos de coprofagia y el lamido frecuente de la zona anal.…”
Section: Caracteristicasunclassified
“…Porphyromonas spp. se ha reportado en enfermedad periodontal y su crecimiento es estimulado por la placa dentobacteriana, en la cual coexiste con otros microorganismos que consumen el oxígeno del medio y generan el potencial redox adecuado para su proliferación, tal como lo reportan Vega y Fernández (20), en su estudio realizado en 30 caninos de diferentes albergues. El género Actinomyces se reporta en enfermedad periodontal y fue aislado en el 8.4% de las muestras.…”
Section: Caracteristicasunclassified
See 1 more Smart Citation